Using "Click‐e‐Bricks" to Make 3D Elastomeric Structures. (30th July 2014) - Morin, Stephen A.; Shevchenko, Yanina; Lessing, Joshua; Kwok, Sen Wai; Shepherd, Robert F.; Stokes, Adam A.; Whitesides, George M.
<x xml:space="preserve">Abstract</x> Soft, 3D elastomeric structures and composite structures are easy to fabricate using click‐e‐bricks, and the internal architecture of these structures together with the capabilities built into the bricks themselves provide mechanical, optical, electrical, and fluidic functions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>